EVALUATING DUPLEX SCAN VERSUS ANKLE-BRACHIAL PRESSURE INDEX IN THE ASSESSMENT OF PERIPHERAL VASCULAR DISEASE AMONG PATIENTS WITH DIABETIC FOOT ULCERS (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Diabetic foot ulcer (DFU) is a significant consequence of diabetes mellitus, frequently linked to underlying peripheral vascular disease (PVD), which impedes wound healing and elevates the risk of amputation. Consequently, the early identification of PVD is essential for prompt intervention and preservation of the limb. Duplex ultrasonography as well as Ankle-Brachial Pressure Index (ABPI) are two prevalent non-invasive techniques for evaluating lower limb arterial insufficiency, although their diagnostic precision differs in diabetic individuals. Aims: The study aims to compare the diagnostic efficacy of Duplex scan and Ankle-Brachial Pressure Index measurements in detecting peripheral vascular disease among patients with diabetic foot ulcers. Materials and Methods: This prospective comparative study was conducted over a period of eight months at the Department of General Surgery in a tertiary care centre in South India. A total of 45 patients with clinically diagnosed DDUs were included based on defined inclusion and exclusion criteria. Detailed history, clinical examination, and laboratory evaluation were performed. Each participant underwent ABPI measurement using a handheld Doppler device. Subsequently, Duplex Doppler Ultrasonography of both lower limbs was carried out to assess arterial flow characteristics, stenosis, and occlusions. The findings were correlated with ABPI values to determine the sensitivity and specificity of ABPI against Duplex as the reference standard. Results: Of the 45 patients, 31 (68.9%) were male and 14 (31.1%) were female, predominantly within the age range of 51–70 years. A duplex scan identified PVD in 28 (62.2%) individuals, whereas the ABPI revealed abnormal values in 24 (53.3%) patients. The average ABPI in those with PVD was 0.62 ± 0.15, whereas it was 0.96 ± 0.08 in individuals with normal Duplex results. The relationship between the Duplex scan and ABPI was statistically significant (p < 0.001). The sensitivity and specificity of the ABPI for identifying PVD were determined to be 85.7% and 90.0%, respectively, yielding an overall diagnostic accuracy of 86.6% in comparison to Duplex ultrasonography. Conclusion: Both Duplex scan as well as ABPI are essential non-invasive methods for identifying PVD in patients with DFUs. Although ABPI functions as a swift and economical screening technique, Duplex ultrasonography provides enhanced diagnostic accuracy and anatomical specificity.